The “Balkan Tea Party” of the Great Powers - V. A. Avatkov (Vestnik MGIMO-Universiteta)
Book Review: Ponomareva E., Arlyapova E. 2024. The Western Balkans in the run-up to and during the current crisis: players and figures. Moscow: Prospekt Publishing House. 318 p. (in Russian)